Pembelajaran Pendidikan Agama Islam Berbasis Digital - Iqbal Syahrijar; Ildira Az Zahra; Udin Supriadi; Agus Fakhruddin (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
In the field of education, the internet as an information manager has become a staple food for people of all ages, from children to adults, to broaden their knowledge. Digitizing education can be done through theapplication of e-learning in teaching and learning activities through the use of technology. This study aims to describe digital-based learning of Islamic religious education. The research method used is descriptive qualitative method. The data collected comes from secondary data through literature analysis from relatedjournals, articles, books and websites. The results of this study indicate that digital-based PAI learning media such as e-learning in the learning process will generate a new will and interest for students, as well as increase motivation in learning. LMS or Learning Management System is a gateway for students to enter a digital-based learning process, which is now being carried out by many educational institutions. Proficiency or lack of understanding of information and communication technology devices is a problem that arises from learning Islamic religious education.